(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines the use of paralinguistic elements from a gender perspective in English and Uzbek languages, focusing on the interaction between non-verbal communication, linguistic expression, social roles, and cultural norms. Gender linguistics provides a theoretical framework for analyzing differences in male and female communication patterns across various age groups and social contexts. Paralinguistic features—such as intonation, tone, pauses, facial expressions, gestures, and body movements—play a crucial role in conveying emotions, social status, and pragmatic intentions beyond the literal meaning of words. The article also explores the cognitive and cultural foundations of paralinguistic communication and highlights the importance of cross-cultural analysis for understanding gender-based differences in communication.